2017
DOI: 10.1136/bmjgast-2017-000153
|View full text |Cite
|
Sign up to set email alerts
|

Weight regain after Roux-en-Y gastric bypass has a large negative impact on the Bariatric Quality of Life Index

Abstract: BackgroundDespite initial successful weight loss, some patients may experience weight regain following Roux-en-Y gastric bypass (RYGB).ObjectiveTo assess the impact of weight regain on bariatric patients’ quality of life (QoL).MethodsThis was a prospective cross-sectional study. Fifty-six consecutive RYGB patients were recruited and divided into weight-regain and weight-stable cohorts. QoL was assessed using the Bariatric Quality of Life (BQL) questionnaire. The BQL Index scores of the weight-regain and weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 45 publications
1
29
0
5
Order By: Relevance
“…Bariatric patients' quality of life is known to be influenced by BMI [33], the extent of weight loss [34] and weight regain [35], and by the persistence of obesity-related diseases [33]. We therefore hypothesized that these factors, along with age, sex, type of procedure and surgical complications might interfere with the postoperative improvement of eating disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Bariatric patients' quality of life is known to be influenced by BMI [33], the extent of weight loss [34] and weight regain [35], and by the persistence of obesity-related diseases [33]. We therefore hypothesized that these factors, along with age, sex, type of procedure and surgical complications might interfere with the postoperative improvement of eating disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the significant weight loss, a proportion of patients experience weight regain or failure of sustained weight loss (Karmali et al, 2013). Studies have shown approximately 15-35% of patient experience insufficient weight loss (less than 50% excess weight loss) or experience significant weight regain (more than 15% of maximal weight loss) following RYGB (Jirapinyo, Abu Dayyeh, & Thompson, 2017). Weight regain may start as early as 1-2 years following surgery.…”
Section: Weight Loss and Weight Regain Following Bariatric Surgerymentioning
confidence: 99%
“…Although bariatric surgery is an effective method for weight loss, less successful outcomes have been reported, including substantial weight regain. Apart from recurrence of medical risks, weight regain may also have a negative impact on the quality of life (QoL) [1]. One and a half to 2 years post-surgery, most patients have either stabilized their weight, or in some cases regained some weight [2].…”
Section: Introductionmentioning
confidence: 99%